Alcohol-related diseases of the oesophagus and stomach - Teyssen, Stephan; Singer, Manfred V. (Best practice & research. Clinical gastroenterology, 2003)
This chapter deals with the most clinically relevant alcohol-related diseases of the oesophagus and stomach. Despite the early findings of W. Beaumont 170 years ago that excessive drinking is associated with gastric bleeding, systematic studies on the action of alcohol and alcoholic beverages on the function of the stomach have only been performed in the last 15 years. The aim of this review is to summarize the data on the effect of acute and chronic alcohol consumption/abuse on the oesophagus and stomach.
Gesehen am 25.04.2022